Pengaruh Kualitas Produk Kerudung Rabbani terhadap Tingkat Kepuasan Konsumen Di Kota Bandung - Tiorida, Ermina; Pramono, Tangguh Dwi; Sifauziah, Sifauziah (Sekolah Tinggi Ilmu Ekonomi Riau, 2019)
Bandung is the center of Muslim fashion in West Java even at the national level. This causes intense business competition in the world of Muslim fashion. To that end, an important role that must be performed by a company is to prioritize product quality and product innovation as a basis for attracting customer so that customer can feel satisfaction from the quality of the products produced. According to Google trends Rabbani trends also experienced a decline in customer interest in the purchasing Muslim fashion. And the results of distributing pre-research questionnaires obtained 70.45% or 31 people were disappointed with the quality of their muslim fashion, this resulted in customer not satisfied with the Rabbani. This study aims to determine how the quality and innovation of Rabbani products to customer satisfaction in the city of Bandung. According to Garvin (1987) there are eight dimensions to test product quality variables, namely performance, features, reliability, conformance, durability, serviceability, aesthetic and perceived quality. Customer satisfaction is measured by three dimensions, namely overall quality, customization and reliability. The study was conducted using quantitative methods. The sampling technique using non-probability sampling techniques and questionnaires were distributed to Rabbani customer in Bandung as many as 150 respondents. Analysis of research data using SEM PLS (Partial Square Structural Equation Modeling) with SmartPLS 3.0 software. the results showed that product quality and innovation had a significant effect on customer satisfaction